Reconstructing Adat, Cultural Heritage, and Islamic Identity: The Role of Majelis Adat Budaya Melayu in Pontianak - Andry Fitriyanto; Syukron Wahyudhi; Bibi Suprianto; Lisyati Fatimah; Muhammad Akbar (Mimbar Agama Budaya, 2026)
It turns out that the reconstruction of customs in the recognition of cultural heritage and Islam has given rise to ethnic supremacy in developing culture in social identity. Customs inherited from generation to generation have moral and ethical values ​​in everyday life. This study questions how the reconstruction of customs in the recognition of cultural and Islamic heritage influences ethnic and religious identity. And how customary reconstruction shapes the recognition of religion and identity within a particular ethnic community. By using qualitative research through interview techniques, observation, and documentation for 3 months in field research. We interviewed nine informan from diverse backgrounds such as the MABM chairman, the MABM general secretary, 2 MABM members, cultural, religious, political, and social figures. This study analyzes several findings related to the reconstruction of customs in the recognition of cultural heritage and Islamic identity, namely: (1) The authority of the Malay Cultural Customary Council over local customs and traditions; (2) the existence of symbols and meanings as a form of pride in social status in the Malay community; (3) the adaptation of Islam to ancestral heritage. These findings reveal the importance of reconstructing customs in recognizing cultural heritage and Islamic identity.